Emotional Intelligence, Intellectual Intelligence and Quality of Work Life on the Performance of the Labuhanbatu Regency Transportation Service Employees - Mayang Firanty Noer; Bayu Eko Broto; Fauziah Hanum (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This type of research is quantitative, and the place of this research is the Department of Transportation of Labuhanbatu Regency. Data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. The population in this study were 84 employees of the Labuhanbatu Regency Transportation Service. The sampling technique used is saturated sampling. Since the number of employees of the Labuhanbatu Regency Transportation Service is 84 people (less than 100 people), all employees are taken as objects of research. The value of Fcount is 30.993> Ftable 2.72 with a significance value of 0.000 <0.05. From these results, it can be concluded that Emotional Intelligence (X1), Intellectual Intelligence (X2), and Quality of Work Life (X3) simultaneously has a positive and significant effect on Employee Performance (Y). The value of R Square from the analysis of the coefficient of determination of 0.538 means that Employee Performance (Y) can be explained by the variables of Emotional Intelligence (X1), Intellectual Intelligence (X2), and Quality of Work Life (X3) of 53.8%, while the remaining 46.2 % can be explained by other variables not examined in this study.